Respuesta :
Answer:
(−4, 12), (1, −3)
Step-by-step explanation:
y = −3x
x^2 −4 = y
so
x^2 −4 = −3x
x^2 + 3x - 4 = 0
(x + 4)(x - 1) = 0
x + 4 = 0; x = -4
x - 1 = 0; x = 1
when x = 1, y = -3(1) = -3
when x = -4, y = -3(-4) = 12
Answer
(-4 , 12), (1 , -3)
ANSWER
(−4,12), (1,−3)
EXPLANATION
The system has equations:
y=−3x
[tex] {x}^{2} - 4 = y[/tex]
We equate the two equations to get:
[tex] {x}^{2} - 4 = - 3x[/tex]
[tex]{x}^{2} + 3x - 4 = 0[/tex]
[tex]{x}^{2} + 4x - x - 4 = 0[/tex]
[tex]x(x + 4) - 1(x + 4) = 0[/tex]
[tex](x + 4)(x - 1) = 0[/tex]
[tex]x = - 4 \: or \: x = 1[/tex]
When x=1,
y=-3(1)=-3
when x=-4, y=-3(-4)=12
The solution is (1,-3) and (-4,12)